2006
DOI: 10.1210/jc.2005-2146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Functional Characteristics of the Human Arg59Ter Insulin-Like Growth Factor I Receptor (IGF1R) Mutation: Implications for a Gene Dosage Effect of the Human IGF1R

Abstract: In vivo and in vitro IGF-I resistance in Arg59Ter subjects and fibroblasts indicates a human IGF1R gene dosage effect involving not only the IGF-IR, but also IGF-IR/IR hybrids. The abundance of both the IGF-IR protein and IGF-IR/IR hybrid receptors may have an impact on human growth, organ function, and glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
2
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 33 publications
7
63
2
6
Order By: Relevance
“…Finally, therapeutic options can be discussed. It has been reported that GH therapy in patients with a heterozygous IGF1R mutation or deletion improves growth and head circumference (18,30,109,130). In the late 1980s, trials with rhIGF-I started in patients with GHR defects.…”
Section: Implications For the Patientmentioning
confidence: 99%
“…Finally, therapeutic options can be discussed. It has been reported that GH therapy in patients with a heterozygous IGF1R mutation or deletion improves growth and head circumference (18,30,109,130). In the late 1980s, trials with rhIGF-I started in patients with GHR defects.…”
Section: Implications For the Patientmentioning
confidence: 99%
“…These were located in exons 2, 7, 11 and 16, respectively. [1][2][3][4][5] Short stature was present in all cases, mild motor and/or speech developmental delay in 4/9 cases and mild intellectual disabilitywith a Wechsler intelligence quotient of 60 -in one case of a patient with a missense mutation in exon 11. This missense mutation was detected in a girl whose mother, a carrier of the same mutation, did not show any neuropsychiatric abnormalities and had normal intelligence.…”
Section: Discussionmentioning
confidence: 93%
“…They were associated with various constellations of clinical findings, including growth deficit, microcephaly, developmental delay, mild facial dysmorphisms and skeletal deformations in affected individuals. [1][2][3][4][5][6][7][8][9][10][11] Usually intrauterine or postnatal growth deficits were moderate to severe in these patients. Notably, cognitive dysfunction of the reported individuals was either moderate, mild or absent.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations